2015
DOI: 10.1128/jb.00232-15
|View full text |Cite
|
Sign up to set email alerts
|

Cofactor Specificity of the Bifunctional Alcohol and Aldehyde Dehydrogenase (AdhE) in Wild-Type and Mutant Clostridium thermocellum and Thermoanaerobacteriumsaccharolyticum

Abstract: Clostridium thermocellum and Thermoanaerobacterium saccharolyticum are thermophilic bacteria that have been engineered to produce ethanol from the cellulose and hemicellulose fractions of biomass, respectively. Although engineered strains of T. saccharolyticum produce ethanol with a yield of 90% of the theoretical maximum, engineered strains of C. thermocellum produce ethanol at lower yields (ϳ50% of the theoretical maximum). In the course of engineering these strains, a number of mutations have been discovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 48 publications
4
69
1
Order By: Relevance
“…Unfortunately, genetic manipulation of nfnAB was impossible in ALK2, as ALK2 already has the Kan and Erm resistance markers, which are the only two antibiotic resistance genes available for T. saccharolyticum. Both ALK2 and M1442 contain mutations in adhE that have been shown to change the cofactor specificity of AdhE from primarily NADH linked to NADPH linked (20). In contrast, the wild-type, LL1144, and LL1145 strains appear to use the NADH-linked ethanol production pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, genetic manipulation of nfnAB was impossible in ALK2, as ALK2 already has the Kan and Erm resistance markers, which are the only two antibiotic resistance genes available for T. saccharolyticum. Both ALK2 and M1442 contain mutations in adhE that have been shown to change the cofactor specificity of AdhE from primarily NADH linked to NADPH linked (20). In contrast, the wild-type, LL1144, and LL1145 strains appear to use the NADH-linked ethanol production pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although mutations in adhE have been shown to produce NADPH-linked ADH activity (20,22,23), another possible source of NADPH-linked ADH activity is the adhA gene, Tsac_2087. It has been shown that in a T. saccharolyticum adhE deletion strain, there were still significant levels of NADPH-linked ADH activity, suggesting that there may be other functional NADPH-linked alcohol dehydrogenases (5).…”
Section: Discussionmentioning
confidence: 99%
“…As presented below, there is evidence suggesting multiple enzymes could perform the ADH reaction in T. saccharolyticum, and AdhE may be necessary only for its ALDH function. We have previously reported the biochemical properties of the C. thermocellum and T. saccharolyticum bifunctional AdhE: wild-type (wt) AdhE is mostly NADH linked for ADH activity in both organisms (12). Deleting adhE in C. thermocellum eliminated Ͼ90% of the ADH activity in cell extracts, suggesting that AdhE is the primary enzyme contributing to ADH activity.…”
mentioning
confidence: 99%
“…All chemicals were reagent grade and obtained from Sigma-Aldrich (St. Louis, MO) or Fisher Scientific (Pittsburgh, PA) unless indicated otherwise. CTFUD rich medium at pH 7.0 and pH 6.0 was used for C. thermocellum and T. saccharolyticum, respectively (22,23). The growth temperature was 55°C for both strains.…”
Section: Methodsmentioning
confidence: 99%
“…Since the alcohol dehydrogenase and acetaldehyde dehydrogenase reactions in C. thermocellum are NADH linked (Fig. 4, NADH based) (22), the NADH-FNOR is more suitable for cofactor balance in C. thermocellum (as opposed to the NADPH-linked NfnAB complex). To test this hypothesis, the tsac_1705 gene was inserted into plasmid pDGO126 (38), and the resulting plasmid was transformed into C. thermocellum.…”
Section: Predicted Structure Of the Tsac_1705 Protein Although Thementioning
confidence: 99%